Non-Abelian Monopoles as the Origin of Dark Matter - Gamboa-Rios, J; Mendez-Ferrada, F (World Scientific Publishing Co. Pte Ltd, 2016)
We suggest that dark matter may be partially constituted by a dilute t Hooft-Polyakov monopoles gas. We reach this conclusion by using the Georgi-Glashow model coupled to a dual kinetic mixing term F G where F is the electromagnetic field and the t Hooft tensor. We show that these monopoles carry both (Maxwell) electric and (Georgi-Glashow) magnetic charges and the electric charge quantization condition is modified in terms of a dimensionless real parameter. This parameter could be determined from milli-charged particle experiments. © 2016 World Scientific Publishing Company.